Fiscal Policy Analysis Bekasi District 2021 Fiscal Year - Susantie, Firdhawati; Ferizaldi, Ferizaldi (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
This study aims to analyze the fiscal policy implemented by the Bekasi Regency local government. The goal is to improve the financial structure by increasing regional financial capacity, which ultimately creates a positive fiscal gap as an indicator of policy success. This study used a qualitative literature review approach, where data was gathered through observations, literature study, and the examination of various secondary sources. The collected data was then analyzed using a descriptive model, which involves describing the data as it is without any alterations or modifications. The findings revealed that the Bekasi Regency Government has put in place various measures to achieve a positive fiscal gap. These include Extensification, which involves maximizing Regional Original Revenue (PAD), and Intensification, where the Tax Object Sale Value (NJOP) is adjusted to optimize the revenue from Fees for the Acquisition of Rights on Land/Building (BPHTB).